The Role of Entrepreneurial Ecosystem Co-Creation in Enhancing Sustainable Business - Simanjuntak, Mariana; Sukresna, I Made (RSF Conference Series: Business, Management and Social Sciences, 2022)
This study focusses on investigating and defining the role of Entrepreneurial Ecosystem Co-Creation in supporting entrepreneurial sustainability and improving marketing performance, especially tourism MSMEs in the face of economic challenges after the covid-19 pandemic. Respondents are entrepreneurs, MSME managers engaged in culinary, entertainment, transportation and accommodation of Toba and Humbang Hasundutan regencies, selected based on Cluster Random Sampling Technique. Data is processed with AMOS SEM. The results showed that the Entrepreneurial Ecosystem Co-Creation (EEC) proved to be strong enough to mediate between Green Entrepreneurial Orientation and Sustainable Entrepreneurial EEC is considered able to improve Marketing Performance (MPF) with a value of P is ,002 (p < 0.05). This study shows that EEC as a mediation is proven to be able to increase MPF and Sustainable Entrepreneurial directly. This study provides future directions for the role model of green entrepreneurship, which provides green services so that it can be a reference for entrepreneurs to create shared values and implement a sustainable green ecosystem in sustainable entrepreneurial management and marketing performance. This study provides future directions for the role model of green entrepreneurship, which provides green services so that it can be a reference for entrepreneurs to create shared values and implement a sustainable green ecosystem in sustainable entrepreneurial management and marketing performance.